BUREAUCRACY IN BEHAVIOR ANALYSIS LICENSING SERVICES INTERFERENCE IN MAKASSAR - *, Hari; Asang, Sulaeman; *, Haselman; Ahmad, Badu (IJRDO - Journal of Applied Management Science, 2015)
This study aimed to analyze the behavior of the bureaucracy in licensing service interruption in Makassar. Research conducted at the Integrated Licensing Agency for Investment and Makassar, and the Department of Industry and Trade of Makassar, data collection is done through observation, interviews and documentation. Data were analyzed using descriptive qualitative analysis. The results showed that the behavior of the bureaucracy in the service of licensing behavior disorders related to aspects of the organization’s objectives in particular with regard to licensing procedures (SOP) has not been reflected in the simplicity of the process, because it involves two agencies and still shows the sectoral ego between them. Aspects of incentives should motivate employees to perform optimally, but this incentive, especially in the form of money has not been budgeted for the second agency. Still the number of complaints over the counter complaint at the agency showed that the accountability of employees in the service is not running optimally. Aspects of power in the context of this research is the signing authority licensing process has been going on delegation of authority to the Chief BPTPM, which were previously signed by the Mayor of Makassar. The strong patriarchal society Makassar, internal bureaucracy and the impact on public services received.